Prevalence of dysmenorrhea and its effect on quality of life among a group of female university students - Unsal, Alaettin (Informa Healthcare, 2010)
The objective was to evaluate the prevalence of dysmenorrhea and determine its effect on health-related quality of life (HRQoL) among a group of female university students. This cross-sectional study was conducted between 15 March and 15 April 2009 at Dumlupinar University, Kutahya, Health High School, Western Turkey. The study group included 623 female students. The severity of dysmenorrhea was determined with a 10-point visual analog scale. The Short Form-36 (SF-36) form was used to determinate HRQoL. Chi-square test, Student's t test, and logistic regression and variance analyses (ANOVA) were used for statistical analyses. The average age of the study group was 20.8 ± 1.8 years (range 17–30). Prevalence of dysmenorrhea was found to be 72.7% and was significantly higher in coffee consumers, females with menstrual bleeding duration ≥7 days, and those who had a positive family history of dysmenorrhea when compared to the others (P < 0.05, for each one). By multivariate analysis, coffee consumption (OR 2.084), menstrual bleeding duration ≥7 days (OR 1.590), and positive family history of dysmenorrhea (OR 3.043) were important risk factors for dysmenorrhea. Except for social functioning, role–emotional, and mental health domains, the SF-36 points received from the other domains were higher in females with dysmenorrhea (for each one P < 0.05). With the exception of the scores received from physical functioning and role–emotional domains, the scores received from the other domains of the SF-36 scale showed a decrease with increasing severity of dysmenorrhea (P < 0.05, for each one). Dysmenorrhea is a common health problem, having negative effects on the HRQoL among university female students.